UNIVERSIDAD, REFORMA Y SOCIEDAD EN AMÉRICA LATINA: Universidad, conocimiento y economía - Villavicencio , Arturo (2024)
The government policy on science and technology and the role assigned to the universities is grounded on a set of inaccurate ideas and misunderstandings about the links between science, technology and research. These ideas have gradually acquired, even in the academic milieu, the status of conventional wisdom in such a way that they legitimize government agencies' action. This paper deals with the tendency of viewing universities as the source of directly applicable knowledge and information on which other entities can build rnarketvalue goods and services. lt takes a critical stand towards converting universities into an economic agent functional to the market sphere. The article concludes that the main role of research activities carried out by universities is to couple research and teaching and that the public good provided by universities is a sense of nacional culture, the creation of a form of social identity and cohesion